Towards a participatory strategy (on and) for mental health: school for comm unity mental health monitors in La Pintana - Encina, Esteban; Minoletti, Alberto (Revista Chilena de Salud Pública, 2017)
The article presents the development and preliminary evaluation of the School for Monitors in Community Mental Health, a pioneering initiative implemented in the Santiago Municipality of La Pintana since 2011 to promote community participation in public health through the training of community mental health monitors. Preliminary data on graduation rates, school attendance, and satisfaction are presented, along with a SWOT analysis. Furthermore, the conditions needed for the establishment of a project of this nature are detailed, with a focus on the tripartite coordination between the Community Mental Health Center (COSAM), University, and community organizations. Limitations and future projections of this initiative are discussed, emphasizing the benefits of community participation for the mental health and well-being challenges currently facing Chile.